2010
DOI: 10.5194/osd-7-291-2010
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Automated gas bubble imaging at sea floor – a new method of in situ gas flux quantification

Abstract: Abstract. Photo-optical systems are common in marine sciences and have been extensively used in coastal and deep-sea research. However, due to technical limitations in the past photo images had to be processed manually or semi-automatically. Recent advances in technology have rapidly improved image recording, storage and processing capabilities which are used in a new concept of automated in situ gas quantification by photo-optical detection. The design for an in situ high-speed image acquisition and automated… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…For the size evaluation, we calculated equivalent spherical bubble diameter using ellipse fitting [ Leifer and MacDonald , ] and area equivalence [ Thomanek et al ., ] approaches. Statistically, both approaches provided consistent result in estimating bubble size, but the equivalent bubble diameter computed using ellipse fitting was systematically lower than that computed with the area equivalence method (with ratio of 0.93:1 for our data) [see Wang and Socolofsky , ].…”
Section: Methodsmentioning
confidence: 99%
“…For the size evaluation, we calculated equivalent spherical bubble diameter using ellipse fitting [ Leifer and MacDonald , ] and area equivalence [ Thomanek et al ., ] approaches. Statistically, both approaches provided consistent result in estimating bubble size, but the equivalent bubble diameter computed using ellipse fitting was systematically lower than that computed with the area equivalence method (with ratio of 0.93:1 for our data) [see Wang and Socolofsky , ].…”
Section: Methodsmentioning
confidence: 99%
“…Using a fast lens, which means a high aperture, is not a solution, because this lowers the depth of field and leads to potentially defocused images. To overcome this problems, so called bubble boxes have been developed (Thomanek et al, 2010). A bubble box as shown in Figure 1 includes a camera, channeling elements to concentrate the bubbles in the cameras depth of focus, and a backlight illumination.…”
Section: Introductionmentioning
confidence: 99%
“…-27-Texas A&M University -Corpus Christi Hydrocarbon fluid seepage has been detected in the thrust faulting regime generated in the Makran subduction zone offshore Pakistan [Ding et al, 2010b] and active gas venting was observed in depths of 1020 m [Thomanek et al, 2010]. The HYFLUX project examined the archive of SAR images with the goal of determining whether the SAR technique of detecting potential gas hydrate bearing areas would be effective on a geologically active margin.…”
Section: Hyflux Final Reportmentioning
confidence: 99%